Use of MTT Assay for Proliferation of U937 Cell Line and its Inter-rater Reliability - Best Taken with a Grain of Salt - Wakode, S.; Trushna, T.; Wakode, N.; Thakare, A.; Bharshankar, R.; Manjunatha, S. (Kathmandu University Medical Journal, 2020)
Background Biomedical research frequently employs immortal human cell lines to study various physiological and pathological topics of interest. An important problem that is often ignored is the question of reliability of observations made while using a particular assay on cell lines, especially MTT Assay. Recent studies have questioned its reliability by highlighting the diverse intracellular environmental factors that affect accuracy of MTT assay results. Objective To assess the inter-rater reliability of MTT assay while observing the differential effect of addition of fetal bovine serum to the culture medium on proliferation of U937 cell line using Intraclass correlation coefficient. Method U937 cell suspension prepared by the tutor to maintain uniformity of immortalized cell line was used. Four trainee investigators who participated in the study underwent rigorous training in pipetting and plating methods for four consecutive days prior to start of the experiment. Each trainee investigator followed the same protocol and all procedures were conducted simultaneously. At the end of the experiment, inter observer reliability was calculated. Result Interrater reliability calculated by using intra class correlation coefficient with two way mixed effect model was found to be poor (p = 0.173). For growth with 10% fetal bovine serum, inter-rater reliability was 0.258 for each item and 0.58 for the average of the triplicates, whereas for 0% fetal bovine serum it was 0.374 for each item and 0.70 for average of the values (p=0.104). Conclusion Though MTT assay is considered the gold standard test for assessment of cell proliferation and viability, the inter-rater reliability of this assay might be poor and needs further investigation.